Negotiating the social contract in urban Africa: Informal food traders in Ghanaian cities - Resnick, Danielle; Sivasubramanian, Bhavna (International Food Policy Research Institute, 2020)
How do cities build a social contract with their diverse constituencies and foster political trust among the urban poor? This study focuses on informal traders, who constitute a major source of food security and employment in urban Africa. Centered on Ghana’s three main cities, we analyze interviews with metropolitan policymakers and a survey of approximately 1,200 informal traders. The findings show that expectations about reciprocity and procedural justice play a key role in shaping the probability of trusting one’s local government. Lower levels of trust were associated with disappointment over the lack of benefits that accompany tax payments to local assemblies. Moreover, those who had experienced harassment by city authorities were less likely to trust their local government. The analysis demonstrates that political trust at the subnational level deserves greater empirical attention, especially as countries continue to deepen decentralization initiatives and cities strive to meet global development goals around inclusivity.